Hush-A-Bye Night: Goodnight Lake Superior : Goodnight Lake Superior - Godin, Thelma Lynne; Eberts, Katie (Ann Arbor, MI : Sleeping Bear Press, 2023)
Rhyming text describes nightfall around Lake Superior as the plants and animals, including humans, that call its shores home begin their nighttime routines.
new kids book 2023 spring.
Ages 2-6.
Keywords: Stories in rhyme; Bedtime -- Fiction; Night -- Fiction; Nature -- Fiction; Lake Superior -- Fiction; Lakes -- Fiction; Stories in rhyme; Picture books